SOSIALISASI STIMULASI DETEKSI INTERVENSI DINI TUMBUH KEMBANG (SDIDTK) DI LINGKUNGAN POSYANDU WILAYAH KERJA PUSKESMAS TAROGONG GARUT DENGAN APLIKASI MOTHER CARES (MOCA) - Desy, Desy Syswianti; Tri Wahyuni (Jurnal Pengabdian Masyarakat DEDIKASI, 2020)
This service activity aims to improve the knowledge and skills of parents with children aged 0-5 years on how to perform Stimulation, Detection, Early Intervention (SDIDTK) using the Mother Cares (MOCA) application. The method used is a lecture accompanied by questions and answers, followed by a simulation of the SDIDTK examination and ending with the practice of examining SDIDTK through the MOCA application. The MOCA application is a new program designed to facilitate parents in conducting stimulation checks, early detection and intervention of growth through PB and BB and development through KPSP. After socialization and practice regarding early detection of growth and development in infants and toddlers, the community is willing to independently detect early growth and development in infants and toddlers via smartphones. With this MOCA application, it is hoped that parents can carry out early detection of children easily independently so that treatment can be carried out as soon as possible if there are delays or discrepancies found during early detection.